International and multidisciplinary scientific collaborations and networks are advancing knowledge about Stevens–Johnson syndrome and toxic epidermal necrolysis. (1st July 2019) - Dodiuk‐Gad, R.P.
Abstract : Linked Article : Carr et al. Br J Dermatol 2019; 181 :166–174 .